Financial analysis of the corporate sector in Ecuador - Villa Maura, César Alfredo; Vargas Ulloa, Diana Evelyn; Merino Villa, Edgar Francisco (mktDESCUBRE, 2018)
The present investigation is carried out to cover the need for a Financial Analysis of the Ecuadorian Corporate Sector, based on the collection, processing and presentation of the results of the 2017 ranking data of the Superintendence of Companies, the institution responsible for controlling and registering companies, the Ecuadorian corporate sector, considered as a set of actors, individuals and legal entities of the private and public sector, which develops its commercial activities within the legal framework determined by the Companies Law. Studies are carried out: Observational, Retrospective, Transversal, Descriptive. The analysis shows that the economic situation of the companies is healthy within all their classifications and groups of technical indicators analyzed, leaving under observation the return on Assets, Assets and Sales, which is not significant, does not make local investment attractive and foreign should be supplemented with state incentives to become the engine of development.